The evalution of stress distributions in 3 and 5 unit dental and implant supported fixed zirconia restorations: Finite element analysis - Guven, Sedat; Eratilla, Veysel; Beydemir, Köksal; Dundar, Serkan (Cumhuriyet University Faculty of Dentistry, 2015)
Purpose: In this study, it is aimed to compare the distribution of stress on teeth and implants in 3-and-5-unit-dental and implant supported zirconia restorations by using finite element analysis. Material and Method: Stress distribution formed in teeth and implants as a result of chewing forces was analyzed in dental and implant (Astra Tech Microthread Osseo Speed, Sweeden) supported models of zirconia restoration with 5-unit placed on the numbers of 43, 44, 45, 46 and 47 and with 3-unit placed on the number of 45, 46 and 47. The study was performed through static nonlinear analysis with the three-dimensional finite element analysis method. Results: The highest and the lowest stress were respectively found on the number of 45 and 47 in 3-unit tooth supported model. The highest and the lowest stress in 5-unit tooth supported model were respectively found on the tooth of number 45 and on the root apex of the implant of number 43. Stress accumulation was observed in the cervical portion of the implant in implantsupported models. Stress accumulation in the tooth-supported model was found less than in implant-supported models Conclusion: The extreme forces on the dental and implant-supported restorations with increased units can reduce survival rate of restorations in mouth. In posterior restorations increased in the number of supported teeth and implant can reduce the destructive forces on teeth and implant and may allow longer period retention of the restorations in the mouth.
Keywords: Finite element analysis; Implant supported prothesis; Zirconia restorations